Outcomes of different aortic arch replacement techniques. Issue 2 (9th December 2019) - Abjigitova, Djamila; Mokhles, Mostafa M.; Papageorgiou, Grigorios; Bekkers, Jos A.; Bogers, Ad J.J.C.
Abstract: Background: Consensus on the best treatment for aortic arch pathology is unresolved due to an emerging variety of procedures. We aimed to compare the outcomes of two major techniques for open aortic arch replacement involving the supra‐aortic branches and to identify the risk factors for specific adverse events. Methods: Between 1974 and 2017, 172 patients were treated with either the en bloc (island, n = 59; 34.3%) or branched graft technique (n = 113, 65.7%). Most of the patients were treated in an emergent/urgent setting (52.4%). Results: Patients who underwent the en bloc procedure had significantly shorter cardiopulmonary bypass (median: 241 vs 271 minutes, P  = .041) and aortic cross clamp times (median: 124 vs 168 minutes, P  = .005) than patients who underwent the separate graft technique. Overall, the hospital mortality was lower in the en bloc group, 8.5% vs 19.5%, although the difference was not significant ( P  = .077). No difference was found in the survival between the separate graft and en bloc groups at 1 (77.0 vs 86.3%), 5 (67.7 vs 66.3%) and 10 years (42.4 vs 51.3%), ( P  = .63). The postoperative stroke rate was comparable between the en bloc and separate graft cohorts (14.3 vs 19.6%, P  = .52). Diabetics and those who underwent an elephant trunk procedure were at a higher risk for reintervention. Conclusions: The separate graft technique, which is more common today, showed no difference from the en bloc technique with regard to hospital mortality and morbidity. Furthermore, the late survival and reintervention rates were similar after both procedures.